Autophagy of OTUD5 destabilizes GPX4 to confer ferroptosis-dependent kidney injury - Chu, Li-Kai; Cao, Xu; Wan, Lin; Diao, Qiang; Zhu, Yu; Kan, Yu; Ye, Li-Li; Mao, Yi-Ming; Dong, Xing-Qiang; Xiong, Qian-Wei; Fu, Ming-Cui; Zhang, Ting; et al. (Nature communications, 2023)
Ferroptosis is an iron-dependent programmed cell death associated with severe kidney diseases, linked to decreased glutathione peroxidase 4 (GPX4). However, the spatial distribution of renal GPX4-mediated ferroptosis and the molecular events causing GPX4 reduction during ischemia-reperfusion (I/R) remain largely unknown. Using spatial transcriptomics, we identify that GPX4 is situated at the interface of the inner cortex and outer medulla, a hyperactive ferroptosis site post-I/R injury. We further discover OTU deubiquitinase 5 (OTUD5) as a GPX4-binding protein that confers ferroptosis resistance by stabilizing GPX4. During I/R, ferroptosis is induced by mTORC1-mediated autophagy, causing OTUD5 degradation and subsequent GPX4 decay. Functionally, OTUD5 deletion intensifies renal tubular cell ferroptosis and exacerbates acute kidney injury, while AAV-mediated OTUD5 delivery mitigates ferroptosis and promotes renal function recovery from I/R injury. Overall, this study highlights a new autophagy-dependent ferroptosis module: hypoxia/ischemia-induced OTUD5 autophagy triggers GPX4 degradation, offering a potential therapeutic avenue for I/R-related kidney diseases. Understanding the role of GPX4 in cell ferroptosis at the interface of the inner cortex and medulla is crucial in the context of renal injury. Here, the authors demonstrate that the OTUD5 interaction with GPX4 is key in resisting ischemia/reperfusion-induced ferroptosis in renal cells, offering a new strategy for treating acute kidney injury.